Method of creating vernacular houses pictograms based on “climate – form” impact and relationship: houses’ pictograms; Part 1 - Radoev, Kliment; Wu, Deng (UNNC, 2020)
The purpose of this paper is to present a method of creation of a pictogram system describing architectural form components of vernacular houses; those components acquire their form due to influences imposed by a particular climatic context. Many books and articles have been written on the topic but they suffer from one of the following disadvantages regarding the current goal: they are too comprehensive and specific or they are oriented towards particular philosophical or cultural thinking. The pictograms proposed in this research are on the other hand based on a global approach of many views of a specific problem such as form, scale, enveloping, openings and others. The research method is based on the existing literature, important guidelines for creating pictograms in general, and a unique investigation of 87 vernacular houses. A template for the extracted data about their form, function, structure, composition and technology is used for this investigation. Following established methods, it is proposed to use (and respectively exclude) some of the climate influences which may or may not be relevant to certain house’s features. A set of pictogram rules has been created and based on them ten houses’ pictograms from different climate zones and different continents were created as a test. The pictogram method of studying vernacular houses provides an important global overview of the most essential house members generated in reaction to the climate. It allows for rough estimation and partial comparison in order to spread an indispensable foundation for future deeper research. This research will ultimately lead to the creation of a world map of vernacular houses’ pictograms as an electronic source, which is further explored in part 2 of this study.